Endoultrasound versus Conventional Image Guided (CT/US) Fine Needle Aspiration in Diagnosis of Pancreatic Malignancy - Hossain, Md Amjad; Chowdhury, Md Abul Kalam; Majumder, Krisna Rani; Alam, AHM Towhidul (Journal of Surgical Sciences, 2021)
Background:The emergence of endoultrasound (EUS) has shown this modality to be an excellent method of detecting and staging lesions in the pancreas with a low rate of complications. Controversy has arisen about whether the approach with the conventional image (CT/US) guided FNA or endoultrasound (EUS) guided FNA is the preferred method to obtain cells from suspicious mass. Objectives:To assess the diagnostic efficacy of endoultrasound guided fine needle aspiration (EUS FNA) versus conventional imageguided fine needle aspiration (CT/US FNA) in pancreatic malignancy. Methodology:Twentyeight cases of clinically suspected patients of pancreatic malignancy were included in the study. Each enrolled patient underwent to either a conventional image guided fine needle aspiration or endoultrasound guided fine needle aspiration of the pancreatic mass for diagnosis of pancreatic malignancy. Data were analyzed with the help of SPSS version 23. Statistical analysis was done by student t-test and Chi square (÷2) test. Statistical significance was set at p<0.05. Result: Diagnostic accuracy in terms of distinguishing the cytopathology was 57.1% in conventional image(CT/US) guided FNA group and 85.7% in EUS guided FNA group. These values were numerically convincing for preferring EUS guided FNA method but was statistically insignificant. Again, if we consider the diagnosis of malignancy alone the values were 35.7% and 64.3% for CT/US guided FNA and EUS guided FNA respectively. This was also not significant statistically. Conclusion:Numerically EUS guided FNA showed better precision in detecting pancreatic malignancy and thereby its accuracy in yielding adequate tissue sample for cytological evaluation and inference. Journal of Surgical Sciences (2020) Vol. 24 (2) : 57-60